Community based intervention to optimize osteoporosis management: randomized controlled trial - Ciaschini Patricia M; Straus Sharon E; Dolovich Lisa R; Goeree Ron A; Leung Karen M; Woods Carol R; Zimmerman Greg M; Majumdar Sumit R; Spadafora Silvana; Fera Luke A; Lee Hui N (BMC Geriatrics, 2010)
Abstract Background Osteoporosis-related fractures are a significant public health concern. Interventions that increase detection and treatment of osteoporosis are underutilized. This pragmatic randomised study was done to evaluate the impact of a multifaceted community-based care program aimed at optimizing evidence-based management in patients at risk for osteoporosis and fractures. Methods This was a 12-month randomized trial performed in Ontario, Canada. Eligible patients were community-dwelling, aged ≥55 years, and identified to be at risk for osteoporosis-related fractures. Two hundred and one patients were allocated to the intervention group or to usual care. Components of the intervention were directed towards primary care physicians and patients and included facilitated bone mineral density testing, patient education and patient-specific recommendations for osteoporosis treatment. The primary outcome was the implementation of appropriate osteoporosis management. Results 101 patients were allocated to intervention and 100 to control. Mean age of participants was 71.9 ± 7.2 years and 94% were women. Pharmacological treatment (alendronate, risedronate, or raloxifene) for osteoporosis was increased by 29% compared to usual care (56% [29/52] vs. 27% [16/60]; relative risk [RR] 2.09, 95% confidence interval [CI] 1.29 to 3.40). More individuals in the intervention group were taking calcium (54% [54/101] vs. 20% [20/100]; RR 2.67, 95% CI 1.74 to 4.12) and vitamin D (33% [33/101] vs. 20% [20/100]; RR 1.63, 95% CI 1.01 to 2.65). Conclusions A multi-faceted community-based intervention improved management of osteoporosis in high risk patients compared with usual care. Trial Registration This trial has been registered with clinicaltrials.gov (ID: NCT00465387)